Does placenta praevia mean placental disease?. (18th April 2012) - Warreth, N; Cooley, S; Gillan, J; Coulter-Smith, S
Abstract : Introduction: Placenta praevia complicates 0.4% of pregnancies and is associated with adverse maternal and neonatal outcome. Implantation over the cervix may differ from placentation implantation in the uterine corpus as the cervix differs in both composition and blood flow. Our hypothesis is that placenta praevia may predispose to placental disease secondary to impaired maternal placental perfusion. Aim: To determine the incidence of placental ischemic disease and fetal hypoxia in cases complicated by placenta praevia. Methods: Retrospective review of all cases of placenta praevia in singleton pregnancies between January 1 st 2005 to December 31 st 2010 in the Rotunda Hospital, Dublin 1. Cases were identified from the computerised maternity records. Maternal placental ischemic disease was defined as uteroplacental insufficiency (UPI), which is the presence of accelerated villous maturation (AVM) or placental infarction. Histological evidence of fetal hypoxia was defined as the presence of nucleated erythroblasts or chorionic villous haemorrhage. Maternal age, ethnicity, parity, previous sections, gestation at delivery, obstetric and neonatal outcome were reviewed. Results: 112 cases of placenta praevia were reviewed. There were 12 multiple pregnancies and these were excluded. Histology was available in 71%. Accelerated villous maturation was present in 38%. This is seven times higher than the reported incidence of AVM in population studies. Placental infarction occurred in 15.5%. Fetal hypoxia was present in 21.1% (15/71). Conclusion: Placenta praevia is associated with increased rates of maternal placental ischaemic disease with further negative implications for fetal wellbeing.